Instructors’ point of view about lesson planning, Semnan Medical University, 2002 - M Saberian (Babol University of Medical Sciences, 2003)
Background and Objective: Designing and having lesson plan is one of the main points in promotion of education quality. Designing is a process determine the goals and recognize the needs, facilities and limitations which exit. This study was done to determine the university instructors’ viewpoint about designing. Methods: This study was done on 53 instructors of Semnan University of Medical Sciences. Data was gathered by a questionnaire with 8 demographic questions and 24 questions for determining the instructors’ viewpoint. Findings: According to the results, 88% of cases were agreement on written lesson planning. 60.4% used lesson plan in teaching and believed that it is effective in promotion of education quality. But, 49.1% were disagreement to be given the lesson plan to the students. Conclusion: Findings showed that positive attitude to lesson planning causes instructors be interested in giving the lesson plan to students. Also, holding lesson-planning workshop for instructor is necessary.